PEMENUHAN HAK PENYANDANG DISABILITAS BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 2016 DI DESA JAGABAYA, KABUPATEN LEBAK - Siti Chadijah; Dwi Kusumo Wardhani (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2021)
Community Service Activities (PKM) in Jagabaya Village by Lecturers of the Faculty of Law, Pamulang University as a form of applying knowledge and experience to realize community progress. By choosing the theme of Fulfilling the Rights of Persons with Disabilities Based on Law Number 8 of 2016 concerning Persons with Disabilities, it is hoped that the government will implement the objectives of the establishment of Law Number 8 of 2016, one of which is by supporting the availability of accessibility. In addition, it is equally important that the surrounding community must also actively participate in realizing equal rights and opportunities for persons with disabilities through empowerment in MSME (Micro, Small and Medium Enterprises) aimed at realizing a quality, independent, and non-discriminatory life. Persons with disabilities as part of Indonesian citizens have the same position, rights and obligations as non-disabled people so that it is appropriate for persons with disabilities to get facilities as an effort to protect against vulnerability to various acts of discrimination and especially protection from various human rights violations.Keywords: Disability, Rights Fulfillment, MSME